Experimental study of the effect of rock blasting with various cutting forms for tunnel excavation using physical model tests - Huaming An; Yushan Song; Deqiang Yang (Archives of Civil Engineering, 2021)
Cutting blasting has been widely used for tunnel excavation. The cutting forms significantly influence the blasting effect. This research focuses on the study of the relationship between cutting forms and blasting effects. Similarity theory is proposed for the experimental study of the rock blasting using small models. Then four experimental modes with different cutting forms are used to study the blasting effect due to the cutting forms. The cutting depth, borehole utilization rate, fragments volume, and average fragment size are analysed. The blasting effects with various cutting forms are compared. The influences of the borehole space and the blasting delay are discussed. It is concluded that the spiral cutting form can produce more fragments and is recommend for the small section tunnel excavation.